2008
DOI: 10.1021/la702024x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayer Compatible with Metal Surface Acoustic Wave Devices on Lithium Niobate

Abstract: The formation of a siloxane self-assembled monolayer (SAM) film on a lithium niobate substrate was investigated for surface acoustic wave (SAW) sensor devices for the detection of hydrogen. The most widely used SAM coupling reagent, octadecyltrichlorosilane, etches aluminum metal features that are integral to sensor devices, due to the formation of high local concentrations of hydrochloric acid. An alternative coupling reagent, octadecyltrimethoxysilane (OTMS), does not show any etching of metal parts. OTMS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…In fact, the chemical reaction with OTS involves the release of Cl atoms that are expected to cause mild reduction of the top BPO layer 21 analogous to surface oxide reduction and corrosion of Al contacts in electronic devices. 22 Remarkably, the amount of oxygen depleted from the BPO layer is comparable to the amount of oxygen required for the Si-Ox interface between BPO and OTS (see the SI for details). We, therefore, infer that the binding process of OTS is self-supported by the pre-existing BPO layer, which enables the success and robustness of our treatment.…”
mentioning
confidence: 93%
“…In fact, the chemical reaction with OTS involves the release of Cl atoms that are expected to cause mild reduction of the top BPO layer 21 analogous to surface oxide reduction and corrosion of Al contacts in electronic devices. 22 Remarkably, the amount of oxygen depleted from the BPO layer is comparable to the amount of oxygen required for the Si-Ox interface between BPO and OTS (see the SI for details). We, therefore, infer that the binding process of OTS is self-supported by the pre-existing BPO layer, which enables the success and robustness of our treatment.…”
mentioning
confidence: 93%
“…Ali et al used 3-mercaptopropyltrimethoxysilane (MPTMS) monolayers on a silicon substrate, to improve the adhesion of gold films on the substrate for biosensing applications [304]. Nihonyanagi et al carried out studies on the formation of a siloxane SAM on a lithium niobate substrate for surface acoustic wave (SAW) devices which are used in the detection of hydrogen gas [305]. Figure 8 shows an aluminum component of this system and the role played by alkylsilane SAMs.…”
Section: Sensor Layers Using Alkylsilane Samsmentioning
confidence: 99%
“…Heterobifunctional reagents such as N-succinimdyl-6-maleimidocaproate react with APS monolayers to expose maleimide functionality, which then can be used in a Michael addition with sulfanyl groups [315,316]. O'Donnel et al reported a slightly different approach for DNA attachment to glass, where they applied a heterobifunctional cross linking agent to incorporate an iodoacetamido group, which was treated with a reduced oligodeoxynucleotide presenting free surface sul- [305]. Adapted from Ref [305].…”
Section: Alkylsilane Sams In Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…This SAM has characteristics that make it compatible with conventional SAW device manufacturing techniques. [8] 3. Surface Chemistry of Carbon Nanotubes and other Nanoporous Carbon Materials.…”
Section: Self-assembled Monolayer Compatible With Metal Surface Acousmentioning
confidence: 99%